Pengaruh Gaya Kepemimpinan Transformasional, Kompensasi, dan Komitmen Organisasional terhadap Kinerja Karyawan - Kristina, Ni Kadek Nopa; Sugianingrat, Ida Ayu Putu Widani; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to partially and simultaneously influence transformational leadership styles, compensation, and organizational commitment on employee performance at the head office of PT. BPR Sukawati Pancakanti in Gianyar. The population in this study were all employees of PT. BPR Sukawati Pancakanti in Gianyar as many as 69 people. Determination of the sample using a saturated sample, so that the entire population is used as a sample, the data is analyzed using multiple linear regression. The results of the analysis show that employee performance is positively and significantly influenced by transformational leadership style, compensation, and organizational commitment at the head office of PT. BPR Sukawati Pancakanti in Gianyar. Suggestions that can be put forward in this research are to PT. BPR Sukawati Pancakanti in Gianyar to further encourage employees to be creative in dealing with the problems they face and to be independent without waiting for orders from the leadership.